Pengaruh Aromaterapi Lavender Dan Rendam Kaki Air Hangat Terhadap Kualitas Tidur Ibu Hamil Trimester III - Syifa Fauzia Sabila Rosyada; Anis Ardiyanti; Diffa Risqa Arisdiani (Lembaga Pengembangan Kinerja Dosen, 2023)
Sleep disorders in the third trimester of pregnant women occur due to the increasing weight of the fetus which results in shortness of breath, back pain and fetal movement which results in sleep disturbances. If left untreated, it will result in complications and disturbances to the mother and fetus. This study aims to determine the effect of lavender aromatherapy and warm water foot soaks on the sleep quality of third-trimester pregnant women in the working area of ​​the Karangayu Health Center. This type of research is a quasi-experimental one group pretest-posttest design. The sample of this research is 49 respondents. This study used the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analysis was performed using the Spearman-rank test for relationship and the Wilcoxon test for influence. The results showed that the majority were aged 20-35 years 65%, high school education 63.3%, housewife work 67.3%, multigravida parity 65.3%, Spearman-rank test showed no relationship between age, education, occupation, and parity on the sleep quality of third trimester pregnant women. the results of the Wilcoxcon test obtained a p value of 0.000, meaning that there was an effect of lavender aromatherapy and warm water foot soaks on the sleep quality of third trimester pregnant women. Suggestion: future research should pay attention to warm water temperature, room, and the same number of respondents.